Peningkatkan Motivasi Belajar Siswa Melalui Bimbingan Kelompok - Kris Sudarti (Jurnal Prakarsa Paedagogia, 2018)
The purpose of this study was to find out whether the efforts to improve motivation to learn through group guidance to Class VII students. H Middle School 1 TrangkilPati semester 2 academic year 2017/2018. PTBK Hypothesis: There are efforts to increase motivation to learn through group guidance to Class VII students. H Trangkil Middle School 1 Pati semester 2 academic year 2017/2018. Research design: 1) planning / planning, 2) acting / acting, 3) observation / observing), 4) reflection / reflection. Research subjects were only 7 students whose learning motivation was low compared to other friends. The reason for choosing class VII. H as a respondent of guidance and counseling actions. Conclusions from the research: 1) PTBK hypothesis which states that there is an effort to increase motivation to learn through group guidance for Class VII students. H Trangkil Pati 1 Middle School in semester 2 of the academic year 2017/2018, tested and proven true. 2) The effectiveness of group guidance services in improving the learning motivation of Class VII students. H Trangkil Pati 1 Middle School in semester 2 of the academic year 2017/2018, tested and proven to be true based on the findings data from the initial conditions to the second cycle there was an increase of 27.86%.